A Hybrid Algorithm of GA + Simplex Method in the WSN Localization. (29th July 2015) - Wang, Feng; Wang, Cong; Wang, ZiZhong; Zhang, Xue-ying
Abstract : Localization provides the key support for wireless sensor networks (WSNs). In order to solve the large-error problem in the third phase and the poor position accuracy of the least square method in the weighted DV-Hop algorithm, a hybrid algorithm of GA + simplex method was proposed in this paper. The weighted DV-Hop position algorithm was applied to estimate the distance between the unknown node and the anchor node in the first and second phase. In the third phase, a hybrid genetic algorithm with the simplex method was proposed to optimize the coordinates of the unknown nodes. In the hybrid genetic algorithm, a fitness function which combined the cost function with the penalty function was built, and the simplex method was used to increase the local search ability of the algorithm. Experiments show that both of the localization accuracy and network coverage rate are improved significantly, and the hybrid algorithm of GA + simplex method is suitable for the WSN localization.